The Newtown Line: Analyzing a Geography of Abandonment in Suburban Philadelphia - DeSimone, Noah (Perceptions, 2019)
My essay involves the investigation of a piece of abandoned rail infrastructure in the Philadelphia suburbs known as the Newtown Line or the Newtown Branch. My piece includes an analysis that delves into the history of this infrastructure as well as the socio-politico-economic and geographic changes in the surrounding region which led to its abandonment. In this research, I discovered that the Newtown Line was largely a smaller, less-significant branch line of the Reading Railroad. As the Reading Railroad operated commuter rail to and from dormitory suburban communities in the 1950s onward, the area which the Newtown Line served remained largely rural. When suburban living became muddled by the rise of post-Fordist tendencies in geography (like shifts in location of workplace) commuting patterns no longer necessitated transportation to and from the suburbs in a Fordist manner. When development came around to the area surrounding Newtown in the 1970s and 1980s, there was no longer a demand for an intracity rail route for commuters. These new suburban residents did not commute in the same way that residents of older suburban communities did, and as a result a substantial base was never created to patronize the Newtown Line. This shift helped secure the line's demise. My conclusion from this research is that townships along the route should encourage the reuse of the rail line as something other than a commuter rail line, such as a bike trail, to reflect its obsolescence.